Qualidade da água do açude Pindobal e avaliação da aplicabilidade de fossa ecológica como alternativa para esgotamento sanitário e conservação de ambientes aquáticos, Mamanguape/Rio Tinto-PB - Carvalho, Rebecca Vanielly Santana de (2021)
Domestic open sewers are the reality of many places, causing soil and water pollution, bad smells, the appearance of insects and the transmission of diseases. In this context, socio-environmental technologies are presented as alternatives for the population without sewage collection, as they are financially and technologically viable. Among these technologies are ecological pits, which treat sewage at the place where it was generated. Therefore, it was proposed to use ecological cesspits of the Banana Circle type as an alternative for the treatment of single-family sewage in two rural communities, in the municipalities of Mamanguape and Rio Tinto, in Paraíba, in order to avoid or alleviate the problems generated by it . Sensitization was also carried out, with workshops and questionnaires to learn about the environmental perception of the residents of the communities. The water from the Pindobal Reservoir, used by the two communities for leisure, irrigation, among others, was collected at three points, in August, September and December 2019. The parameters pH, turbidity, total dissolved solids, conductivity, oxygen were analyzed dissolved, ammonia, nitrite, nitrate, phosphate, total phosphorus, chlorophyll, total coliforms and Escherichia coli. the results of the water quality of the weir were analyzed temporally and spatially in accordance with CONAMA Resolution 357/2005, presenting pH and OD outside the established standards, and Consolidation Ordinance 5/2017, presenting pH, turbidity, E. coli and total non-standard coliforms. Statistical analyzes were performed using the ANOVA and Kruskal Wallys tests, in order to verify if there were significant differences. Due to the pandemic of COVID 19, only four ecological pits were implanted. None of them had problems such as bad smell, the appearance of insects or overflow, having been approved by the people who implanted them.